Media sosial memengaruhi body image dan gangguan makan pada remaja - Malonda, Nancy Swanida Henriette; Punuh, Maureen Irinne; Pondagitan, Alpinia Shinta; Tomastola, Yohanis; Anastasya, Solideo; Bidara, Christa; Taroreh, Putri (Holistik Jurnal Kesehatan, 2026)
Background: Social media can negatively impact body image and increase the risk of eating disorders in adolescents, yet these platforms are widely used. Adolescents tend to worry about their appearance in response to social media content. Negative body image is a risk factor for eating disorders, which can impact adolescents' nutritional status, leading to undernutrition or overnutrition. Purpose: To determine the influence of social media on body image and eating disorders in adolescents. Method:  The study design used a descriptive analytical approach with a cross-sectional approach. The sample consisted of 211 eleventh-grade students from Senior High School in Tondano, Minahasa Regency, taken using a total sampling technique. Body image was measured using the MBSRQ-AS, eating disorders were measured using the EAT-26 questionnaire, and social media was measured using the ASMC Scale questionnaire. Results: The majority of respondents had a positive body image (85.8%), were not at risk for eating disorders (54%), and reported a high influence from social media (78.7%). Statistical analysis using the Spearman rank sum test showed a positive correlation between digital media and body image (p=0.000; 0.261) and eating disorders (p=0.045; 0.138). The influence of social media can lead to body image dissatisfaction and eating disorders. Therefore, interventions such as improving social media literacy are recommended to prevent negative impacts on adolescents' mindsets and attitudes. Conclusion: Social media exposure is significantly associated with body image disturbance and eating disorders in adolescents.   Keywords: Body Image; Eating Disorders; Social Media.   Pendahuluan: Media sosial memiliki dampak negatif terhadap body image dan gangguan makan remaja, namun remaja cenderung selalu menggunakan platform ini. Oleh karena itu, penting untuk mengidentifikasi strategi yang dapat mengurangi dampak buruk media sosial terhadap kesehatan mental remaja. Tujuan: Untuk mengetahui pengaruh media sosial terhadap body image dan gangguan makan pada remaja.    Metode: Rancangan penelitian menggunakan deskriptif korelatif dengan pendekatan cross-sectional. Sampel berjumlah 211 remaja kelas XI SMAN 1, SMAN 2, dan SMAN 3 di Tondano kabupaten Minahasa yang diambil dengan menggunakan teknik total sampling. Body image diukur menggunakan MBSRQ-AS, gangguan perilaku makan diukur menggunakan kuesioner EAT-26 dan pengaruh media sosial menggunakan kuesioner ASMC scale. Hasil: Mayoritas responden memiliki body image positif (85.8 %), tidak berisiko mengalami gangguan perilaku makan (54 %), dan memiliki pengaruh tinggi (78.7%) dari media sosial. Hasil analisis statistik menggunakan uji Spearman rank, diketahui bahwa terdapat korelasi positif antara media digital terhadap body image (p=0.000; 0.261) dan gangguan makan (p=0.045; 0.138). Pengaruh media sosial dapat menyebabkan ketidakpuasan akan body image dan gangguan perilaku makan, sehingga direkomendasikan untuk dilakukan intervensi berupa peningkatan literasi penggunaan media sosial agar tidak menimbulkan efek negatif terhadap pola pikir dan sikap remaja. Simpulan: Paparan media sosial secara signifikan berhubungan dengan gangguan body image dan gangguan makan pada remaja.               Kata Kunci: Body Image; Gangguan Makan; Media Sosial.